Strigolactone derivatives for potential crop enhancement applications - Screpanti, Claudio; Fonné-Pfister, Raymonde; Lumbroso, Alexandre; Rendine, Stefano; Lachia, Mathilde; De Mesmaeker, Alain (Bioorganic & medicinal chemistry letters, 2016)
[Display omitted] New technologies able to mitigate the main abiotic stresses (i.e., drought, salinity, cold and heat) represent a substantial opportunity to contribute to a sustainable increase of agricultural production. In this context, the recently discovered phytohormone strigolactone is an important area of study which can underpin the quest for new anti-stress technologies. The pleiotropic roles played by strigolactones in plant growth/development and in plant adaptation to environmental changes can pave the way for new innovative crop enhancement applications. Although a significant scientific effort has been dedicated to the strigolactone subject, an updated review with emphasis on the crop protection perspective was missing. This paper aims to analyze the advancement in different areas of the strigolactone domain and the implications for agronomical applications.